Sosialisasi Pemberdayaan Masyarakat Melalui Ekonomi Kreatif untuk Meningkatkan Perekonomian di Desa Manunggang Jae Kota Padangsidimpuan - Masdelima Azizah Sormin; Fitriani; Benny Sofyan Samosir; Yani Sukriah sireg; Imelda Sari Harahap; Rani Annisa Dalimunthe; Windy Ariska Harahap; Amir Mahmud; Darmadi Erwin Harahap (Jurnal Transformasi Pendidikan Indonesia, 2025)
This study aims to examine the socialization of community empowerment through creative economy as an effort to improve the economy in Manunggang Jae Village, Padangsidimpuan City. Community empowerment through creative economy has great potential to improve economic welfare, especially in rural areas. Manunggang Jae Village has the potential of natural and cultural resources that can be developed through creative economic activities, such as handicrafts, local culinary, and technology-based creative industries. In this study, a participatory approach was used to involve the community in every stage of the empowerment process, from socialization to program implementation. The results of the study show that with effective socialization and appropriate training, the community can better understand the potential of the creative economy and apply it to create jobs, increase income, and strengthen the village economy. Therefore, strengthening community capacity and support from various parties are the keys to success in improving the economy in the village.